2022
DOI: 10.1145/3526112
|View full text |Cite
|
Sign up to set email alerts
|

Mental State Attribution to Robots: A Systematic Review of Conceptions, Methods, and Findings

Abstract: The topic of mental state attribution to robots has been approached by researchers from a variety of disciplines, including psychology, neuroscience, computer science, and philosophy. As a consequence, the empirical studies that have been conducted so far exhibit considerable diversity in terms of how the phenomenon is described and how it is approached from a theoretical and methodological standpoint. This literature review addresses the need for a shared scientific understanding of mental state attribution t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 198 publications
1
26
0
Order By: Relevance
“…Overall, these results are in line with previous studies ( Hackel et al, 2014 ; Martini et al, 2016 ; Di Dio et al, 2018 , 2020a , b ; Manzi et al, 2020b ) reporting that different agents, or even the same agent with different characteristics (e.g., different types of robots; Manzi et al, 2020b ), can evoke different – although diminished – attributions of human mental traits. Importantly, the tendency to attribute mental states to robots is also determined by factors such as people’s age, motivation, cultural background, and attitude toward robots, as well as the behavior, appearance, and identity of the robot ( Marchesi et al, 2019 ; Thellman et al, 2022 ). Likewise, in a recent study, Manzi et al (2021c) showed that humans are particularly sensitive to the design of robots in terms of attribution of mental qualities; in fact, even when robots differ slightly in their physical appearance, the dissimilar design evokes different mental properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these results are in line with previous studies ( Hackel et al, 2014 ; Martini et al, 2016 ; Di Dio et al, 2018 , 2020a , b ; Manzi et al, 2020b ) reporting that different agents, or even the same agent with different characteristics (e.g., different types of robots; Manzi et al, 2020b ), can evoke different – although diminished – attributions of human mental traits. Importantly, the tendency to attribute mental states to robots is also determined by factors such as people’s age, motivation, cultural background, and attitude toward robots, as well as the behavior, appearance, and identity of the robot ( Marchesi et al, 2019 ; Thellman et al, 2022 ). Likewise, in a recent study, Manzi et al (2021c) showed that humans are particularly sensitive to the design of robots in terms of attribution of mental qualities; in fact, even when robots differ slightly in their physical appearance, the dissimilar design evokes different mental properties.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, regardless of religious background, preschoolers attribute qualities such as omniscience to the mind of God, thus perceiving God’s mind at a higher epistemic level than humans’ minds ( Nyhof and Johnson, 2017 ; Di Dio et al, 2018 ). Several studies have focused also on the attribution of minds to robotic agents (for a review, see Thellman et al, 2022 ) and observed that adults are more inclined to ascribe greater mental states to robots characterized by human-like physical features ( Dario et al, 2001 ; MacDorman et al, 2005 ; Kiesler et al, 2008 ; Krach et al, 2008 ; Bartneck et al, 2009 ; Fink et al, 2012 ; Gray and Wegner, 2012 ; Airenti, 2015 ; Złotowski et al, 2015 ; Thellman et al, 2017 ; Wiese and Weis, 2020 ; Manzi et al, 2020b , 2021a , b , c ). This tendency has also been found in children over the age of five, who are likely to attribute more mental states to robots with more human-like features; in contrast, younger children tend to anthropomorphize by giving less importance to the human aspect of the robotic agent ( Di Dio et al, 2020a , b ; Manzi et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several authors explored how humans interpret the behaviors of a robot and whether they refer to mental states in their explanations and predictions of robot behaviors (Thellman & Ziemke, 2020; for a review see Thellman et al, 2022). In a similar vein, Marchesi and colleagues (Marchesi et al, 2019) have developed the InStance Test (IST) to probe adoption of the intentional stance towards robots.…”
Section: Examining Social Cognition With the Use Of Humanoid Robots -...mentioning
confidence: 99%
“…), and biological (e.g., Is the robot alive?). A recent meta-analysis revealed that age is a factor in whether children attribute mental states to robots (Thellman, de Graaf, & Ziemke, 2022). Although the findings were mixed, most studies reported that people of all ages attribute mental states to robots.…”
mentioning
confidence: 99%